Structural Determinants of the Natural Rate of Unemployment in Canada. (IMF Working Papers; Working Paper, 1989)
This paper presents empirical estimates of the policy and structural determinants of the natural rate of unemployment in Canada. The paper begins with a discussion of structural features of the economy which impinge on the adjustment of real wages to their equilibrium level. Estimates are presented showing how the generosity of the unemployment insurance system is related to past levels of unemployment. The empirical results indicate that government policies have been largely responsible for changes in the natural rate, and hence can contribute to a reduction in the natural rate in the medium term.